Respuesta :

1. Distribute the -2x with the (x+3)
2.Multiply (x+1) and (x-2) which is (x2- x -2)
So far it should look like (-2x^2 -6x) - (x^2-x-2)
3. Distribute out the negative
Should look like this -2x^2 -6x - x^2+x+2
4. Lastly combine like terms

Your result should be:
-3x^2 - 5x + 2

Hope this helps!

-2x(x + 3) - (x + 1)(x - 2)


//Distribute

= (-2x² - 6x) - (x² - 2x + x - 2)


// Combine like terms

= (-2x² - 6x) - (x² - x - 2)


// Open brackets

= -2x² - 6x - x² + x + 2


//Combine like terms

= - 3x² - 5x + 2

//Factorise

= (1 - 3x)(x + 2)


Answer:  (1 - 3x)(x + 2)